The reduction of school failure. Pending issue of the spanish education system - Vaquero García, Alberto (Avances en Supervisión Educativa, 2011)
The indicators commonly used to measure school failure demonstrate the clear need for Spain to improve its high rate of early school leavers, educational level of the population from 20 to 24 years and reading comprehension difficulties of students. Despite the actions carried out in the last twenty years, has not yet achieved a breakthrough in the results. The aim of this paper is to analyze the current situation for the Spanish case in comparative perspective and a set of measures to reduce school failure, one of the pending Spanish educational system.